Investigate the physical and rheological properties of asphalt binders modified with barium sulfate nanoparticles. (2nd December 2019) - Hamedi, Gholam Hossein; Sahraei, Ali; Halimi, Navid
Abstract: The aim of this study is to investigate the physical and rheological properties of modified asphalt binders with barium sulfate (BaSO4 ) nanoparticles. The penetration grade test and the softening point test on the controlled and modified asphalt binders showed that the presence of nanoparticles improved the physical properties of asphalt binders. Dynamic shear rheometer (DSR) test was performed on the main and modified asphalt binders in unaged and short-term aged modes. The asphalt binders containing 2% of nanoparticles in each of the unaged and short-term aged modes have the maximum value of rutting parameter at all temperatures.